KINERJA APARATUR DESA TERHADAP PENGELOLAAN ARSIP DI KANTOR DESA BUNTU BUANGIN KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Muhammad Fatiril Haq; Kamaruddin Sellang; Muhammad Ikbal; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the performance of village officials on the management of village archives in Buntu Buangin Village, Pitu Riase District, Sidenreng Rappang Regency. The population in this study was 658 residents in Buntu Buangin Village, Watang Pulu District, Sidenreng Rappang Regency with sampling using the slovin formula so that a sample of 87 people was obtained. This type of research is descriptive quantitative. Data collection techniques used in this study were observation and questionnaires. The data analysis technique used is using the IBM SPSS statistics 21.0 Application. The results of this study indicate that the Village Apparatus Performance 57.3% has less role. Village Archives Governance 59.16% less role. The Performance of the Village Apparatus